Value Added Tax treatment in Project Procurement drop shipments - Warpenius, Joonas (My University, 2023)
Procurement has been evolving during the recent decades from mainly administrative function towards more value adding and strategic. This development trajectory has its roots in accelerated trends of globalization, digitalization, and outsourcing. Moreover, increased market liberalization and cost pressures have affected the procurement function’s overall positioning. In the thesis case company Metso Outotec Finland Oy, a subsidiary of Metso corporation, project procurement has a distinctive business operating model while acting in an intermediary position between manufacturers or suppliers and customers. Direct goods drop shipment deliveries are arranged from Finland between aforementioned parties without them having any direct connection. This can be seen as a practical application of global value chains. Considering the current operating model with multiple stakeholders and cross-border movements of goods, the value added tax treatment is understandably challenging. Consequently, the thesis has its focus in identifying economically and operationally crucial phases and situations as well as risk mitigating opportunities from project procurement point of view in value added tax context. In addition, reasonable contractual aspects in the case company’s various supply chains are suggested. Based on the conducted research literature overview, supply chain management and legal or fiscal objectives have not usually been aligned in logistics domain, which is a relevant research gap from the thesis point of view. Thus, combining the procurement, logistics and legislation forms the basis and theoretical framework for the thesis. In addition, the strategic usage of Incoterms® is only rarely considered topic in scientific publications. This is another interesting aspect to which this thesis is contributing. Value added tax seems to be a secondary object of attention even though it is identified potentially causing considerable additional costs for projects, irrational logistical arrangements, delays and even reputational damage and sanctions. As the value added tax is not based on voluntariness the compliance must be ensured and supported with internal alignment, division of responsibilities, information technology capabilities and corporate level guidelines for instance. Moreover, for personnel determining value added tax treatment the sufficient level of knowledge and competence should be assured as there exist large number of factors affecting the overall treatment. Among these, for example, prevailing trade conditions, legislation under which the power to dispose is transferred, parties organizing transportations and conducting goods clearances, contractual factors such as chosen Incoterms® clauses in the chain and potential existence of value added tax registrations. The European Union model of value-added taxation is central in this review as a dominant model for indirect tax applications globally. However, the lack of harmonization among European Union member states is causing additional issues and challenges from legislation point of view due to value added tax relying solely on directives in European Union and having some overlapping points with customs legislation. Central aspects seem to be related to the tax collecting method taking place in multiple phases and emphasis on the destination principle. Also, the possibility to apply zero rate only once in the chain of transactions unless intra-EU trade is further combined with export procedures is a determining feature.

Hankinta on viime vuosikymmeninä kehittynyt hallinnollisesta toiminnosta kohti arvoa luovaa strategisempaa roolia. Tämä kehityskulku liittyy erityisesti kiihtyneeseen globalisaatioon, digitalisaation luomiin kyvykkyyksiin ja ydinosaamisen keskittymistä seuranneeseen ulkoistamiseen. Lisäksi hankintafunktion asemaan ovat erottamattomasti vaikuttaneet markkinoiden laaja vapautuminen ja kasvaneet kustannuspaineet. Tutkielman toimeksiantajalla, Metso konserniin kuuluvalla tytäryhtiö Metso Outotec Finland Oy:llä, on erottuva liiketoimintamalli projektihankinnan osalta toimiessa valmistajan tai tavarantoimittajan ja loppuasiakkaan välissä. Tässä toimintamallissa suorat tavarantoimitukset organisoidaan Suomesta käsin ilman, että aiemmin mainituilla tahoilla on minkäänlaista suoraa linkkiä keskenään. Tämä voidaan käytännössä nähdä eräänlaisena globaalien arvoketjujen ilmentymänä. Kohdeyrityksen nykyiseen liiketoimintamalliin liittyy tyypillisesti useita sidosryhmiä sekä rajat ylittäviä tavarantoimituksia, minkä vuoksi arvonlisäverotus on haastava osa-alue. Tutkielma keskittyykin tunnistamaan taloudellisesti ja toiminnallisesti olennaisia vaiheita ja tilanteita sekä kartoittamaan riskinhallintamahdollisuuksia projektihankinnan osalta arvonlisäverotuksen kontekstissa. Lisäksi yleispäteviä toimitusketjuihin soveltuvia sopimusteknisiä seikkoja kartoitetaan ja ehdotetaan kokonaistarkasteluun pohjautuen. Kirjallisuuskatsauksen perusteella toimitusketjujen johtaminen ja oikeudelliset tai verotukselliset tavoitteet sekä linjaukset eivät tyypillisesti ole yhtenäisiä logistiikkafunktiossa sovellettaessa. Tämä on myös tutkielman kannalta keskeinen tutkimusaukko. Hankinnan, logistiikan ja lainsäädännöllisten näkökulmien ja tarpeiden yhdistäminen muodostaakin tutkielman teoreettisen viitekehyksen. Myös Incoterms® -lausekkeiden strateginen hyödyntäminen on harvinainen aihe tieteellisten julkaisujen kohdalla. Tämä onkin toinen mielenkiintoinen puute, johon tutkielma pyrkii omalta osaltaan vastaamaan. Arvonlisäverotus vaikuttaa jäävän jossain määrin toissijaiseksi huomionkohteeksi, vaikka siihen liittyvät potentiaalisesti huomattavatkin kustannusvaikutukset, epärationaaliset logistiset järjestelyt ja myöhästymiset sekä jopa mainehaitat seuraamuksineen. Arvonlisäverotus ei ole myöskään vapaaehtoinen asia, minkä myötä sääntelyn noudattaminen on varmistettava ja tuettava esimerkiksi sisäisellä yhtenäisyydellä, selkeällä vastuunjaolla, riittävillä tietojärjestelmäkyvykkyyksillä ja korporaatiotason linjauksilla. Lisäksi on perusteltua huolehtia arvonlisäverotuksen kanssa tekemisissä olevan henkilöstön osaamisesta ja kilpailukyvystä, koska sääntelyn noudattamisen toteutuminen riippuu hyvin monista kokonaisuuteen vaikuttavista tekijöistä. Näihin lukeutuvat esimerkiksi vallitsevat kaupan ehdot, määräysvallan siirron kohdalla sovellettava lainsäädäntö, kuljetuksia ja tavaraselvityksiä tekevät tahot, sopimustekniset asiat esimerkiksi Incoterms® -lausekkeiden muodossa ja mahdolliset arvonlisäverorekisteröinnit. Euroopan unionin malli on keskeinen tarkastelun kannalta, koska se on maailmanlaajuisestikin hallitseva ja sovellettu perusta arvonlisäverotuksen toteuttamiselle. Lainsäädännöllisiä haasteita aiheuttavat kuitenkin harmonisoinnin puute jäsenmaiden kesken arvonlisäverotuksen perustuessa EU:n direktiiveihin sekä päällekkäisyydet tullilainsäädännön kanssa. Keskeisiä määrittäviä tekijöitä vaikuttavat olevan arvonlisäveron määräytyminen useissa arvonluonnin vaiheissa ja kohdeperiaatteen painottaminen tarkastelussa. Lisäksi määrittävä tekijä on vain yhden nollaverokannan soveltuminen pitkissä ketjuissa EU:n sisällä, ellei ketjuun sisällytetä vientiä.
Keywords: project procurement, VAT, EU-legislation, Incoterms®, logistics, tax aligned supply chains, global value chains